Nuclear power plant instrumentation and control systems for safety and security - Yastrebenetsky, Michael; Kharchenko, Vyacheslav (IGI Global, 2014)
"This book evaluates the risks inherent to nuclear power and methods of preventing accidents through computer control systems and other such emerging technologies. Students and scholars as well as operators and designers will find useful insight into the latest security technologies with the potential to make the future of nuclear energy clean, safe, and reliable"--Resumé vydavatele
Keywords: jaderná bezpečnost; jaderné elektrárny; jaderné elektrárny -- Ukrajina; digitální řídicí systémy; nuclear safety; nuclear power plants; nuclear power plants -- Ukraine; digital control systems; sborníky; elektronické knihy; papers of several authors; electronic books